Curcumin Nanoparticle Enhances the Anticancer Effect of Cisplatin by Inhibiting PI3K/AKT and JAK/STAT3 Pathway in Rat Ovarian Carcinoma Induced by DMBA - Sandhiutami, Ni Made Dwi; Arozal, Wawaimuli; Louisa, Melva; Rahmat, Deni; Wuyung, Puspita Eka (Frontiers in Pharmacology, 2021)
Cisplatin has been used for decades for the treatment of ovarian cancer. However, despite its potent anticancer effect, cisplatin's efficacy as a single agent was inadequate in patients with advanced stage. Curcumin has been shown to sensitize cisplatin activity in several cancer models. However, the low bioavailability of curcumin has limited its anticancer potential. Hence, nano-formulation of curcumin was developed to increase its therapeutic efficacy in ovarian cancer. The objective of this study was to investigate the mechanism of curcumin nanoparticles given in combination with cisplatin in rat ovarian carcinoma induced by dimethylbenz(a)anthracene (DMBA). The administration of cisplatin and nanocurcumin resulted in a significant reduction in ovarian tumor volume and weight. Furthermore, there were reduction in expressions of Ki67, TGF-β, PI3K, and Akt phosphorylation. Co-treatment of cisplatin and nanocurcumin also reduced JAK expression, STAT3 phosphorylation, and reduced IL-6 concentrations. Altogether, nanocurcumin, given as a co-treatment with cisplatin has therapeutic potential in ovarian cancer models by inhibiting proliferation through downregulation of PI3K/Akt and JAK/STAT3 signaling pathways.